25.9k views
2 votes
Solve for (g).

−3+5+6g=11−3g

g= ?

User Hippout
by
4.8k points

2 Answers

6 votes

Answer:

1

Explanation:

bc khan

User Ziv Kesten
by
5.2k points
0 votes

Answer:

g=1

Explanation:

Given equation is \[−3+5+6g=11−3g\]

Simplifying, \[2+6g=11−3g\]

Bringing all the terms containing g to the left hand side and the numeric terms to the right hand side,

\[6g + 3g=11−2\]

=> \[(6 + 3)g=9\]

In other words, \[g=\frac{9}{9}\]

Or, g = 1

The given equation is satisfied for g=1.

Validation:

Left hand side of the equation: -3+5+6 = 8

Right hand side of the equation: 11-3 = 8

User Beiller
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.